Utilization of Social Media to Find Arabic Learning Resources A Use and Gratifications Theory Analysis on Students of MAN 1 Yogyakarta - Atik Syakiroh; Iqbal Ahsanul Aula (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aims to determine how MAN 1 Yogyakarta students use social media to search for Arabic language learning resources and how the Use and Gratifications theory which states that media cannot influence the content someone chooses, including as supporting media for learning, can explain students' behavior in using it. social media for learning Arabic can explain students' behavior in using social media to learn Arabic. This research also aims to find out how MAN 1 Yogyakarta students benefit from using social media to find Arabic language learning resources. This research uses a qualitative-descriptive method to understand other people's understanding of a phenomenon. Data collection in this research was by questionnaire and then the data was analyzed thematically. The results of this research found several ways for students to obtain and use learning information on social media. Students are influenced by the teacher to follow content related to learning Arabic, then the algorithm on social media used by students directs students to related content according to students' interest in content in the form of images or videos, students carry out their own searches, especially on social media Instagram and YouTube. The use and gratification theory can explain students' behavior in using social media as a medium to search for Arabic language learning resources, students have full control over the choice of social media used to search for learning resources, so that social media can be used as a learning medium to help students in independent learning .